Revival Duration and Determinants of ASEAN Machinery Trade During COVID-19 Pandemic and the Global Financial Crisis. Issue 4 (16th March 2023) - Chang, Chia-Lin; Wang, Yu-Hui; Chang, Kuo-I
ABSTRACT: This study performs survival analysis to evaluate duration of revived and new machinery import and the hazard ratios (HRs) of covariates related to the global financial crisis (GFC) and COVID-19 pandemic in the Association of Southeast Asian Nations (ASEAN). The results indicate that large tariff margins decreased the possibility of disruption (HR: 0.8024) to Japanese import from ASEAN countries after revived during the COVID-19 pandemic and increased the possibility of disruption (HR: 1.0338) to Chinese import from ASEAN countries of new import during the GFC.